Preparation, Functionality, and Application of Metal Oxide‐coated Noble Metal Nanoparticles. Issue 4 (13th June 2016) - Liu, Shuhua; Regulacio, Michelle D.; Tee, Si Yin; Khin, Yin Win; Teng, Choon Peng; Koh, Leng Duei; Guan, Guijian; Han, Ming‐Yong
Abstract: With their remarkable properties and wide‐ranging applications, nanostructures of noble metals and metal oxides have been receiving significantly increased attention in recent years. The desire to combine the properties of these two functional materials for specific applications has naturally prompted research in the design and synthesis of novel nanocomposites, consisting of both noble metal and metal‐oxide components. In this review, particular attention is given to core–shell type metal oxide‐coated noble metal nanostructures (i.e., metal@oxide), which display potential utility in applications, including photothermal therapy, catalytic conversions, photocatalysis, molecular sensing, and photovoltaics. Emerging research directions and areas are envisioned at the end to solicit more attention and work in this regard. Abstract : This paper reviews the synthesis of metal oxide‐coated noble metal nanoparticles and their potential utility in biomedicine, photovoltaics, small molecule sensing, catalytic conversions, and photocatalytic reactions. Emerging research directions that are envisioned include plasmonic electrochromism, defect‐enhanced photocatalysis, oxide shell synthesis, and functional oxide film fabrication.